Scale‐dependent foraging ecology of a marine top predator modelled using passive acoustic data. (31st July 2013) - Pirotta, Enrico; Thompson, Paul M.; Miller, Peter I.; Brookes, Kate L.; Cheney, Barbara; Barton, Tim R.; Graham, Isla M.; Lusseau, David; Costa, Daniel
Summary Understanding which environmental factors drive foraging preferences is critical for the development of effective management measures, but resource use patterns may emerge from processes that occur at different spatial and temporal scales. Direct observations of foraging are also especially challenging in marine predators, but passive acoustic techniques provide opportunities to study the behaviour of echolocating species over a range of scales. We used an extensive passive acoustic data set to investigate the distribution and temporal dynamics of foraging in bottlenose dolphins using the Moray Firth (Scotland, UK). Echolocation buzzes were identified with a mixture model of detected echolocation inter‐click intervals and used as a proxy of foraging activity. A robust modelling approach accounting for autocorrelation in the data was then used to evaluate which environmental factors were associated with the observed dynamics at two different spatial and temporal scales. At a broad scale, foraging varied seasonally and was also affected by seabed slope and shelf‐sea fronts. At a finer scale, we identified variation in seasonal use and local interactions with tidal processes. Foraging was best predicted at a daily scale, accounting for site specificity in the shape of the estimated relationships. This study demonstrates how passive acoustic data can be used to understand foraging ecology in echolocating species and provides a robust analytical procedure for describing spatio‐temporal patterns. Associations between foraging and environmental characteristics varied according to spatial and temporal scale, highlighting the need for a multi‐scale approach. Our results indicate that dolphins respond to coarser scale temporal dynamics, but have a detailed understanding of finer‐scale spatial distribution of resources.